Processo de diagnóstico audiológico de pacientes de um centro especializado em reabilitação auditiva pediátrica - Siqueira, Daniela Moreira de (2023)
After a failed retest, the child is referred for audiological diagnosis, which must be carried out up to six months of age, with ABR, which is considered the gold standard exam in pediatric audiological diagnosis. Difficulties can occur in the process from screening to diagnosis and therefore, it is important to know the family's journey from neonatal hearing screening to diagnosis. Objective: To characterize the audiological diagnosis process of children treated at a Specialized Rehabilitation Center in the city of São Paulo. Method: All medical records of children who attended the service for audiological diagnosis in the years 2019 to 2021 were analyzed, identifying audiological characteristics, age at the start of care and conclusion of the diagnosis. Results: The medical records of a total of 660 children with an average age of 8.17 months were analyzed. Regarding the place of referral, 41.52% (n=274) came from the Maternity Hospital and 58.48% (n=386) from the Health Network in general. The risk indicator for hearing loss was present in 61.8% (n=408) of the children. A total of 79.7% (n=526) of children completed diagnostic assessment tests at the service. Among those who completed the diagnosis, 53.4% (n=281) had some type and degree of hearing loss. Among the children who completed the audiological diagnosis, 22.3% had sensorineural hearing loss, 15.6% had conductive hearing loss and only 1.14% had mixed hearing loss. Conclusion: Children referred by the maternity ward have a significantly younger age at which the diagnosis is completed than children referred by the network; there is no difference in the diagnosis completion rate between the two groups of children; children referred by the maternity ward had a higher percentage of hearing loss; a significant number of children who were referred by the network still arrive at the service without information or without taking the UNHS